2022
DOI: 10.2217/fmb-2021-0193
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Healthcare Providers’ Perceptions and Attitude on Antimicrobial Resistance, Prescription and Stewardship Programs

Abstract: Background: A successful antimicrobial stewardship program (ASP) is sustained through improving antimicrobial prescribing by changing prescribing behavior. This requires a better understanding of hospital stakeholders’ views regarding antimicrobial resistance (AMR), antimicrobial use and participation in ASP activities. Objectives: Identify perceptions and attitudes among physicians and pharmacists in a public hospital toward AMR, prescription and ASP. Methods: A questionnaire consisting of 45 items was distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Eleven studies each identified the absence of leadership and minimal governmental support [ 27 , 28 , 35 42 ], and a lack of reliable laboratory infrastructure and microbiology laboratory support as challenges to effective ASP implementation [ 28 , 29 , 31 , 35 , 36 , 38 , 40 , 42 45 ]. Other identified barriers included inadequate orientation and training on ASP including rational antimicrobial use [ 27 , 30 , 36 , 41 , 44 , 46 ], prescribers’ negative attitudes to changes in antibiotic practices [ 27 , 30 , 33 , 35 , 37 , 43 , 47 ], and a lack of dedicated ASP funds [ 28 , 32 , 33 , 36 , 37 , 41 ]. Five studies each cited the absence of approved national guidelines or educational programs [ 27 , 36 , 43 , 45 , 48 ], and time constraints for prescribers [ 28 , 30 , 36 , 41 , 48 ] as barriers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies each identified the absence of leadership and minimal governmental support [ 27 , 28 , 35 42 ], and a lack of reliable laboratory infrastructure and microbiology laboratory support as challenges to effective ASP implementation [ 28 , 29 , 31 , 35 , 36 , 38 , 40 , 42 45 ]. Other identified barriers included inadequate orientation and training on ASP including rational antimicrobial use [ 27 , 30 , 36 , 41 , 44 , 46 ], prescribers’ negative attitudes to changes in antibiotic practices [ 27 , 30 , 33 , 35 , 37 , 43 , 47 ], and a lack of dedicated ASP funds [ 28 , 32 , 33 , 36 , 37 , 41 ]. Five studies each cited the absence of approved national guidelines or educational programs [ 27 , 36 , 43 , 45 , 48 ], and time constraints for prescribers [ 28 , 30 , 36 , 41 , 48 ] as barriers.…”
Section: Resultsmentioning
confidence: 99%
“…Six of these studies (29%, 6/21) reported on all three elements: knowledge, attitude, and practice [ 27 , 45 , 47 , 50 – 52 ], and six others exclusively assessed ASP practice compliance [ 32 , 53 57 ]. The majority of the studies revealed that prescribers (physicians or pharmacists) had a sub-optimal knowledge of ASP and its basic principles [ 31 , 45 , 47 , 51 , 52 , 58 ]. However, four studies stated that prescribers had sufficient knowledge of the correct antibiotic indication (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ASPs often establish a restricted formulary, which limits the available antibiotic options for physicians. They may need to adhere to specific guidelines and protocols when selecting antibiotics, restricting their freedom to prescribe broader-spectrum or newer antibiotics [9].…”
Section: Introductionmentioning
confidence: 99%